Tenoumer impact crater, Mauritania: Impact melt genesis from a lithologically diverse target. (February 2016) - Schultze, Dina Simona; Jourdan, Fred; Hecht, Lutz; Reimold, Wolf Uwe; Schmitt, Ralf‐Thomas
Abstract: Impact melt rocks from the 1.9 km diameter, simple bowl‐shaped Tenoumer impact crater in Mauritania have been analyzed chemically and petrologically. They are heterogeneous and can be subdivided into three types based on melt matrix color, occurrence of lithic clast components, amount of vesiculation (melt degassing), different proportions of carbonate melt mingled into silicate melt, and bulk rock chemical composition. These heterogeneities have two main causes (1) due to the small size of the impact crater, there was probably no coherent melt pool where a homogeneous mixture of melts, derived from different target lithologies, could be created; and (2) melt rock heterogeneity occurring at the thin section scale is due to fast cooling during and after the dynamic ejection and emplacement process. The overall period of crystal growth from these diverse melts was extremely short, which provides a further indication that complete chemical equilibration of the phases could not be achieved in such short time. Melt mixing processes involved in the generation of impact melts are, thus, recorded in nonequilibrium growth features. Variable mixing processes between chemically different melt phases and the formation of hybrid melts can be observed even at millimeter scales. Due to extreme cooling rates, different mixing and mingling stages are preserved in the varied parageneses of matrix minerals and in the mineral chemistry of microlites. 40 Ar 39 Ar step‐heating chronology on specimens from three melt rock samples yielded five concordant inverse isochron ages. The inverse isochron plots show that minute amounts of inherited 40 Ar* are present in the system. We calculated a weighted mean age of 1.57 ± 0.14 Ma for these new results. This preferred age represents a refinement from the previous range of 21 ka to 2.5 Ma ages based on K/Ar and fission track dating.